Surveys of 12 California crops for phytoseiid predatory mites show changes compared to earlier studies - Grafton-Cardwell, Elizabeth E.; Bentley, Walter; Bianchi, Mary; Cave, Frances E.; Elkins, Rachel; Godfrey, Larry; Gu, Ping; Haviland, David; Headrick, David; Hoddle, Mark; McMurtry, James; Murrietta, Maria; et al. (My University, 2020)
Phytoseiid mites are key predators in agricultural crops. However, not all species regulate pest populations below economic thresholds, and therefore knowledge of which species are associated with particular crops aids pest control recommendations. Surveys of 12 crops across six geographical regions of California demonstrated that phytoseiid species varied by crop and geographical location, with subtropical crops exhibiting the lowest species diversity and grape the greatest. The western predatory mite, Galendromus occidentalis, long cited as a dominant species in California crops, was not found to be the major species in most situations. Euseius stipulatus, a species introduced in the 1970s, was found in the surveyed crops in many areas of the state and appears to be displacing E. hibisci along the south coast.
Keywords: Phytoseiidae; Amblyseius Swirskii; Predatory Mites